2021
DOI: 10.1111/jfpp.15770
|View full text |Cite
|
Sign up to set email alerts
|

Impact of radiofrequency disinfestation on Tribolium castaneum (Herbst) in wheat flour and its influence on the functional characteristics of wheat flour

Abstract: Wheat flour is the ideal sustenance in food processing and the cornerstone of essential staple foods, universally. In the current lifestyle, people prefer sustenance that is ready to use and available on the market. In this context, storing wheat flour in a good environment and protecting it from external factors is a big challenge (Xu et al., 2018). The shelf-life of wheat flour is confined to few months because of insect infestation, due to contamination during packaging and climatic conditions that result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Also, the mortality was highest at the lowest electrode height and conveyor speed because lowering the electrode spacing increases the electric field intensity in treated products (Jiao et al, 2014; Li et al, 2017) and lowering the conveyor speed increases the exposure time. Similar results of RF showing mortality against Tribolium castaneum were reported by Indumathi et al (2021). However, RF treatment of C. serratus has not been reported yet.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Also, the mortality was highest at the lowest electrode height and conveyor speed because lowering the electrode spacing increases the electric field intensity in treated products (Jiao et al, 2014; Li et al, 2017) and lowering the conveyor speed increases the exposure time. Similar results of RF showing mortality against Tribolium castaneum were reported by Indumathi et al (2021). However, RF treatment of C. serratus has not been reported yet.…”
Section: Resultssupporting
confidence: 89%
“…A generator with two flat-plate parallel rectangular electrodes and an applicator is part of the RF system. Based on the results of the preliminary study (Indumathi et al, 2021), three electrode heights of 180, 200, and 220 mm, and two conveyor speeds of 5 and 7.5 m/h were fixed for this study. The peanut samples were placed in Petri plates (200 × 30 mm) without lids and passed between the electrodes by means of a conveyor (Figure 1) and exposed to an alternating electric field with a high voltage (5 kV) at the fixed combinations of electrode height and conveyor speed.…”
Section: Rf Treatmentmentioning
confidence: 99%
“…Saka et al (2021) evaluated the effect of RF processing on the sedimentation value, falling number, phenolic content, antioxidant activity, and farinograph and extensograph properties of white and whole wheat flours and found that the RF process did not cause a significant change in the physicochemical and rheological properties. (Indumathi et al, 2021) characterized the functional characteristics of RF‐treated whole wheat flour and found that the water absorption capacity, oil absorption capacity, emulsion capacity, emulsion stability, and viscosity of RF‐treated wheat flour was noted to be slightly higher than RF‐untreated wheat flour. The foaming capacity and stability of RF‐treated wheat flour was found to be impaired with RF treatment due to uncoiled structure of protein.…”
Section: Introductionmentioning
confidence: 99%